Perancangan Dan Implementasi Sistem Informasi Pembayaran Pada Perguruan Tinggi Menggunakan Web Services Metode H2H Dari Perbankan - Iis Pradesan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2017)
Technology has great influence in all aspects of human life from commercial needs, to be used as a mere entertainment tool. The technology has also affected the banking activity, the customers no longer have to face to face with the teller, simply with a smartphone and internet connection then all banking activities are resolved on the spot. One form of development of banking technology that has been released at this time is the payment system Host to Host (H2H), this system will be connected through the internet network directly with the server (host) owned by an agency, so that the request made to the data banking transactions can be responded realtime. One of the institutions that can utilize H2H among other universities related to the payment activities conducted by the students. But H2H must be bridged an interface/application that serves as a web services that certainly facilitate in communication with H2H. Therefore, this research is aimed at designing and implementing Web Service with H2H method from banking, while the research method used is descriptive with RUP and UML information system development methodology as a tool in modeling and web-based application using Laravel framework in its development stage.